Fostering SMEs innovation performance development in Saudi Arabia considering vision 2030 - Al-Tayyar; Saud, Raed; Abd Rahman, Azmawani; Ali, Mass Hareeza; Kazaure, Mansur Ahmed (Science and Engineering Research Support Society, 2020)
The objective of this paper is to examine how SMEs in Saudi Arabia can fostered in the economy through innovation, performance and development. It specifically emphasizes on how Saudi Arabia’s vision 2030 can be achieve through the alignment of IT and technological goals. SMEs in Saudi Arabia face with various challenges caused by lack of access to the advance technology. In order to achieve the research objectives and answering the research questions, the paper critically evaluated the role of SMEs in achieving vision 2030 by assessing aspects such as job creation, the gross domestic product, service and industry creation and business innovations. It also looked at how SMEs can tap into the technological and IT resources in working towards these goals. Finally, the paper explored the challenges faced by the SMEs in terms of achieving these goals before giving recommendations. The main findings from the paper were that innovation in IT and technology encourages the growth of small & medium enterprises that will help in the achievement of Saudi Arabia’s vision 2030.